1986
DOI: 10.1073/pnas.83.23.8972
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric model of the photosynthetic unit of Ectothiorhodospira halochloris

Abstract: A stoichiometric model of the photosynthetic unit of Ectothiorhodospira halochloris has been obtained by means of scanning transmission electron microscope mass determination and mass mapping in conjunction with polyacrylamide gel electrophoresis. One reaction center, consisting of four single polypeptides, including one cytochrome, is surrounded by six identical light-harvesting complexes, each containing three polypeptides with 2:2:2 stoichiometry. This stoichiometric model was incorporated into the three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…While we cannot offer any definitive model, our data are compatible with a ringlike structure like that proposed for the photosynthetic membranes of Bchl b-containing Rhodopseudomonas viridis and Ectothiorhodospira halochloris (31)(32)(33)(34). The latter structure was deduced by scanning transmission electron microscopy to be formed of a ring of six identical light-harvesting complexes, each containing three polypeptides with (aJ32y2) stoichiometry (34).…”
Section: Discussionmentioning
confidence: 48%
“…While we cannot offer any definitive model, our data are compatible with a ringlike structure like that proposed for the photosynthetic membranes of Bchl b-containing Rhodopseudomonas viridis and Ectothiorhodospira halochloris (31)(32)(33)(34). The latter structure was deduced by scanning transmission electron microscopy to be formed of a ring of six identical light-harvesting complexes, each containing three polypeptides with (aJ32y2) stoichiometry (34).…”
Section: Discussionmentioning
confidence: 48%
“…Biological significance Early electron microscopy and digital image processing at low resolution (40-50 A) of negatively stained photosynthetic membranes from Rhodopseudomonas viridis (Miller, 1982;Stark et al, 1984) and Ectothiorhodospira halochloris (Engelhardt et al, 1986), which contain BChl b as the major photosynthetic pigment, revealed the membranes to be composed of hexagonally packed 120 A particles which appeared to contain six to 12 lightharvesting units (these organisms possess only LHC I) arranged in a ring around a central reaction centre. Each unit of the ring was suggested to be composed of an ax3-heterodimer, yielding a value of 24 mol BChl b/mol reaction centre.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that PufX could act as a symmetry breaker to prevent the clustering of RC-LH1 complexes into large hexagonal arrangements, as observed for several species of purple bacteria without pufX (6,8,15,46). Due to this suggestion, PufX-induced core dimerization would facilitate indirectly the functional interplay of RC-LH1 core complexes with other components of the photosynthetic unit like LH2 and bc 1 complex.…”
Section: Figmentioning
confidence: 99%